含间隙平面连杆机构动态特性研究 - 王国庆; 刘宏昭 (Jixie chuandong)
This paper takes account of the boundary condition of elements of a joint with clearance when contact occur, by using the nonlinear spring damper formulation to model the resulting reaction force between the elements of clearance joint. The dynamic response of a revolute joint in a four-bar mechanism with a clearance is investigated. When the resulting equations of motion are solved numerically, they show the elements of a clearance joint keeping continuous deformation contact when the mechanism works at high speed.